Краевые задачи для уравнения теплопроводности с дробной производной в граничных условиях и разностные методы их численной реализации - Шхануков, М.Х.; Керфов, А.А.; Березовский, А.А. (Український математичний журнал, 1993)
Розглядаються крайові задачі для рівняння теплопровідності з дробовою похідною в крайових умовах. Задачі такого типу одержуємо при оцінюванні теплових процесів з допомогою однови- мірної теплофізичної моделі двошарової системи (покриття-основа) нестаціонарною тепловою течією. Доведена коректність розглядуваної задачі, побудована однопараметрична сім’я різницевих схем, встановлена стійкість і збіжність різницевих схем у рівномірній метриці. Boundary-value problems for the heat conduction equation are considered in the case where the boundary conditions contain a fractional derivative. Problems of this type arise when the heat processes are simulated by a nonstationary heat flow by using the one-dimensional thermal model of a two-layer system (coating — base). It is proved that the problem under consideration is correct. A one-parameter family of difference schemes is constructed; it is shown that these schemes are stable and convergent in the uniform metric.